Analisis dan karakteristik hidrokarbon normal alkana pada sedimen pantai Makassar - Muhammad Syahrir; Hasri Hasri; Pince Salempa (Seminar Nasional LP2M UNM, 2019)
Based on salinity and water temperature quality standards at number of station locations are still within the specified quality standard range, except at station 7 (TL3) Tello River Estuary, with a very high level of supply of contaminants from organic waste, because it is a watershed from TPAS Antang, waste from PLTU activies and heavy motorized vehicle traffic lanes and the existence of Makassar Industrial Zone (KIMA). The highest turbidity at station 8 (TL2) located in the vicinity of the Tello River Upper based on quality standards has shown a high level of pollution because it is close to the PLTU and motorized vehicle traffic lanes, while the lowest turbidity content at station 3 (AK1) is located around recreation areas / Akkarena Beach) still meets the conditions set. The results of hydrocarbon fractionation by column chromatography using silica gel: alumina (1:1) and each sediment station showed varying levels of aliphatic fractions containing various hydrocarbons. The THK/EBO values vary where the lowest station 6 (TR2) is located near the Makassar Transtudio Mall and the highest station 5 (TR1) which is also located near Makassar Transtudio Mall. This means that microorganism activity high enough to degrade hydrocarbons in the station area. The F1/F2 ratio results also show varying values at each sediment are highest, which indicates that station 1 (JB4) sediment and station 4 (AK2) sediment are the highest, which indicates that station 1 (JB4) sediments are sourced from anthropogenic processes while station 4 (AK2) sediments sourced from not anthropogenic, which occurs through natural processes.